Сучасні польсько-українські бої за історію - Трофимович, Володимир Васильович; Trofymovych, Volodymyr V. (Східноєвропейський національний університет імені Лесі Українки, 2019)
Nowadays, Ukrainians and Poles are apparently experiencing the worst period of their relationship since the early 90's of the twentieth century. Contradictions can not be exhausted fast, because they are generated by the deep processes of the evolution of national identity with the positioning of both peoples in a changing world. In modern Ukrainian-Polish relations, history played a disproportionate dominant role. In Ukraine, we observe active forming of national identity, accompanied by the creation of a pantheon of heroes in national liberation competitions that accelerated and radicalized by Russian aggression. In Poland, the renaissance of national identity began, with the revival of conflict in the assessment of the entire Polish-Ukrainian history, canonization of a certain perception of her tragic pages, for example, Volyn tragedy of 1943, which most Polish society describes as genocide. After the coming to power of the "Prawo i Sprawiedliwość" party, official Warsaw depicts Ukrainians as "criminal nationalists and collaborators of the Third Reich" who allegedly bear all responsibility for the Volyn events of 1943-1944 and criticized the heroism policy of Stepan Bandera, the OUN and the UPA , but it rejects this approach when it comes to the Craiova Army, the Polish non-communist underground, the Polish emigration circles, and Polish nationalism. However, the main problem is not in the differences in the interpretation of events in the history of Ukraine and Poland by politicians and society, but that the ruling party "Prawo i Sprawiedliwość" has set the present and future of Ukrainian-Polish relations in dependence on the acceptance or denial by the official Kiev of the Polish interpretation of historical memory. And this is already unacceptable for Ukrainians who live on the eve of the formation of the Ukrainian state and the formation of Ukrainian identity.
Keywords: Волинь-43; Volyn-43